Exploring the tail of patented invention value distributions - Dietmar Harhoff; Frederic M. Scherer; Katrin Vopel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Patent renewal studies reveal a highly rightward-skewed distribution of patent values. Our approach elicits valuations approximating those of the patented invention. This paper focuses on the full-term patents of the application year 1977 held by West German and U.S. residents. The tail of skewed distributions values account for a large fraction of the cumulative value over all observations. Several tests were conducted to pin down more precisely the nature of the high-value tail distribution. Three highly skew alternatives were evaluated by graphical and maximum likelihood techniques: the two-parameter log normal, the one-parameter Pareto-Levy, and the three-parameter Singh-Maddala distribution. A two-parameter log normal distribution appears to provide the best fit to our patented invention value data. – – Wir analysieren die Verteilung der Erträge aus patentierten Erfindungen unter Nutzung von Daten, die in einer direkten Befragung der Patentinhaber ermittelt wurden. Das Papier konzentriert sich auf Patente deutscher Anmelder mit Anmeldungsjahr 1977, die die volle Laufzeit durch Zahlen der jährlichen Verlängerungsgebühren erreichten. Einige wenige besonders wertvolle Patente in unserem Datensatz stellen den Großteil des Gesamtwerts der Patente. Mehrere Tests werden durchgeführt um die Art der Verteilung der Erträge näher zu bestimmen. Dabei werden die Pareto-, die Singh-Maddala und die Lognormal-Verteilung verwendet. Die Lognormal-Verteilung scheint die von uns ermittelten Erträge aus patentierten Erfindungen am besten zu beschreiben.
Keywords: 330